Isolated Splenic Lymphangiomas Presenting in an Infant with Isolated Anaemia - Ameer Kakaje; Raghad Mujahed; Othman Hamdan (Case Reports in Medicine)
Lymphangiomas are benign tumours of lymphatic vessels which are not linked with the normal lymphatic vessels. Their symptoms usually depend on their location and size as they can compress or block adjacent organs. We present a 9-month-old girl with isolated cavernous lymphangiomas of the spleen, a rare variable of lymphangiomas, with no symptoms. She had an isolated anaemia which could only be explained by the hypersplenism caused by the lymphangiomas. Such a presentation has been very rarely reported in the literature and not mainly in children. Furthermore, this case also illustrates imaging of hypersplenism related to lymphangiomas.